Factor analysis of reporting sexual harassment among students in East Java - Fithri, Rizma; Thohar, Syafruddin Faisal (Psychology, Evaluation, and Technology in Educational Research, 2024)
Sexual harassment is an act of sexuality in the form of physical or non-physical touching that can occur in various spheres of the environment, such as social or educational. However, not all individuals dare to report acts of sexual harassment. The purpose of this study was to determine the factors that may influence the reporting of acts of sexual harassment against students in East Java. This study uses a quantitative and qualitative approach. The research subjects totaled 102 people from a predetermined population using a probability sampling technique. The results of this study indicate that the experience of sexual harassment (sig. of the change 0.000 < 0.05) and cognitive perceptions/opinions (sig. of the change 0.054 > 0.05) are factors that influence the reporting of acts of sexual harassment against students in East Java . This shows that there are many students who have experienced sexual harassment, and the action that is most often taken is to report the perpetrator.